Artificial Intelligence in Public Administration – Supporting Administrative Decisions - Fejes, Erzsébet; Futó, Iván (Public Finance Quarterly, 2021)
Artificial intelligence (AI) is an increasingly popular concept, although it is often used only as a marketing tool to label activities that are very far from AI. The purpose of this article is to show what artificial intelligence (AI) tools - expert systems - can actually be used for administrative decision in public administration. The end of the administrative decision must be justified in detail according to the legal regulations. Expert systems do this. The other large group of AI tools, solutions based on machine learning, act as black boxes, mapping input data to output data, so the reason for the solution is unknown. Therefore, these tools are not suitable for direct, administrative decision, but can support office work with expert systems. In this article, we present the operation of expert systems through examples.